AKTIVITAS PLP DASAR SEBAGAI SOLUSI PENGENALAN LINGKUNGAN DI SEKOLAH DASAR NEGERI - Asmitha Purnama Sari; Ratnawati (Jurnal Riset Guru Indonesia, 2024)
Basic PLP is a compulsory course for students to train students to get to know the real world of teaching before really plunging into the world of education, the main activity in the basic PLP course is field practice by observing the school environment accompanied by reflective action under the guidance and supervision of the guidance lecturer. The implementation of PLP 1 aims to fulfill the task of students knowing the school environment, class, teacher duties and how the teacher gives lessons to students. and knowing the conditions that exist in the school environment, students can express ideas for the progress of the school when students later work directly in the school where students are assigned. The implementation of this PLP uses a qualitative descriptive method carried out with a block system that is traveled for 16 days. 4 days on campus and 12 days at school with an implementation time of 5 hours 40 minutes per day. Based on the results of direct observation, it shows that the discipline of the school community has been carried out well. The relationship between school members is good. And the relationship between students / students behaves very well all. With the introduction of the school field at UPT SD Negeri 16 bangkala barat, you can find out the school profile, school management, school culture and culture. strengthening character education. As well as observations of curricular, co-curricular and extracurricular activities.